Endogenous Growth in a Spatial Economy: The Impact of Globalization on Innovations and Convergence. (May 2021) - Broitman, Dani; Czamanski, Daniel
In this article we explore the claim that spatial interactions among cities are significant drivers of their growth. We assert that reallocation of ideas among cities is a source of improved allocation of resources. We propose a closed economy, agent-based model that is in constant flux. It is populated by autonomous agents that compete and adjust constantly their behavior in reaction to the conditions they perceive. The economy is a dynamic, self-organizing system. We focus on the intensity of globalization as the critical economic process that explains differences in convergence and divergence in the system. The means by which the extent of globalization affects the long-run performance of economies is the geographic reach of new ideas and their conversion into innovations. The question that plays out in our model is the relative influence of globalization and the localized entrepreneurial ecology on innovation. When the globalization is weak, new firms are limited by the market value of their own city. As the globalization strengthens, more and more new firms belong to the global playground. We demonstrate that in line with empirical literature, the gross domestic product of our urban system increases greatly with the increase in globalization level.